Process optimisation and parametric effects on synthesis of lipase immobilised carbonaceous catalyst for conversion of rubber seed oil to biodiesel. (15th November 2018) - Dhawane, Sumit H.; Kumar, Tarkeshwar; Halder, Gopinath
Graphical abstract: Highlights: The use of waste derived AC as a support for lipase immobilisation is studied. The immobilisation process is optimised for maximum enzyme loading and catalytic activity. Initial protein concentration and pH affects the immobilisation significantly. The enzyme loaded AC shows higher catalytic activity in transesterification. Cost-effective biodiesel can be produced by obtained optimised conditions. Abstract: Enzymatic transesterification for biodiesel synthesis have gained significant attention due to green and advantageous process over alkali and acid catalysed reactions. In this view, the present study elucidates the synthesis of carbonaceous catalyst support for immobilisation of lipase enzyme towards its use as heterogeneous biocatalyst in biodiesel synthesis. The study mainly emphasised on the optimisation of parametric conditions for catalyst synthesis process towards maximisation of adsorption capacity and catalytic activity in transesterification. The parametric effects on immobilisation process were studied to identify the significance of individual parameter using taguchi approach. The significance of each parameter was tested by ANOVA study and confirmed by estimating contribution factor. The analysis illustrates that initial concentration, pH and time affects the adsorption capacity significantly. However, the catalytic activity in transesterification is affected significantly by catalyst preparation conditions like temperature, pH and initial concentration. The optimised condition evaluated for catalyst preparation to achieve maximum adsorption capacity and biodiesel yield were: initial concentration 400 ppm, temperature 30 °C, time 120 min and pH 6. Thus, the study revealed that indigenously prepared carbon supported lipase enzyme at optimised conditions were effective in catalysing the methanolysis of rubber seed oil to achieve the renewable biodiesel fuel. The study has also shown that taguchi approach was effective in identifying the significant parameters affecting the immobilisation process and achieving optimised condition for cost-effective synthesis of catalyst to ultimately minimise the cost of biodiesel synthesis process.